2019
DOI: 10.19128/turje.609073
|View full text |Cite
|
Sign up to set email alerts
|

Akran değerlendirmede analitik rubrikle ve genel izlenimle yapılan puanlamaların incelenmesi

Abstract: The aim of this research was to analyze and compare analytic rubric and general impression scoring in peer assessment. A total of 66 university students participated in the study and six of them were chosen as peer raters on a voluntary basis. In the research, students were supposed to prepare a sample study within the scope of scientific research methods course and were also expected to present their studies in class. While the students were giving a presentation, their course instructor and peer raters condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…There has been some research developing rubrics for assessments of students' competence, for example [4], and [14]. Analytical rubric has been found to better reveal students' ability [4] whereas a meta-analysis of 75 studies by [14] reported that rubrics offered reliable scoring assessment to enhance student performance specifically for analytic, topic-specific and complemented rubrics with examples, and that it also potentially improves learning. However, as different classes/courses have specific characteristics, such as student level, needs, and materials, those rubrics cannot be directly adopted, especially for peer assessment.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some research developing rubrics for assessments of students' competence, for example [4], and [14]. Analytical rubric has been found to better reveal students' ability [4] whereas a meta-analysis of 75 studies by [14] reported that rubrics offered reliable scoring assessment to enhance student performance specifically for analytic, topic-specific and complemented rubrics with examples, and that it also potentially improves learning. However, as different classes/courses have specific characteristics, such as student level, needs, and materials, those rubrics cannot be directly adopted, especially for peer assessment.…”
Section: Introductionmentioning
confidence: 99%